MANAJEMEN PENGEMBANGAN SDM KEPENDIDIKAN BERMUTU DI PERGURUAN TINGGI - Rahman, Nur Ali (El-HARAKAH (TERAKREDITASI), 2006)
The evolving culture of our contemporary society continues to have an ongoing and profound effect on the practice of educational human resources management in university, because a good society can be performed through a good performance of individual. Human resources with a good performance can be a product of an excellent university. In realities, the excellent universities are changed by the good human resources including educational staffs, practicing central-office administrators and building principals who want to become more familiar with the field of human resources management. This article tries to discuss the management of quality educational human resources development in university. The effort to develop the quality of an education institution should start with the mapping of education resources which gears into several strategies in accordance with the condition of the institution. Furthermore, such an effort is oriented to meet the need of the institution.Â Â Budaya masyarakat kontemporer kita yang terus berkembang terus memiliki efek yang terus berlanjut dan mendalam terhadap praktik pengelolaan sumber daya manusia pendidikan di universitas, karena masyarakat yang baik dapat dilakukan melalui kinerja individu yang baik. Sumber daya manusia dengan kinerja yang baik bisa menjadi produk universitas unggulan. Kenyataannya, universitas unggulan diubah oleh sumber daya manusia yang baik termasuk tenaga kependidikan, praktisi kantor pusat dan kepala sekolah yang ingin lebih mengenal bidang pengelolaan sumber daya manusia. Artikel ini mencoba membahas pengelolaan pengembangan sumber daya manusia pendidikan yang berkualitas di universitas. Upaya pengembangan kualitas lembaga pendidikan harus dimulai dengan pemetaan sumber daya pendidikan yang disesuaikan dengan beberapa strategi sesuai dengan kondisi institusi. Selanjutnya, upaya semacam itu berorientasi untuk memenuhi kebutuhan institusi.